ANALISIS TINGKAT PENGETAHUAN MASYARAKAT TENTANG HUKUM WARIS ISLAM DI DESA SUMILLAN KECAMATAN ALLA KABUPATEN ENREKANG - Mustaring Mustaring; Asmila Muhani (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2018)
This study aims to: 1) Obtain data on the level of knowledge of the villagers Sumillan District of Alla Enrekang on Islamic law, 2) Obtain data on people's knowledge of how the division of inheritance based on the Islamic law of inheritance in the Village Sumillan District of Alla Enrekang, 3) Obtain data on the efforts made by the government Sumillan Rural District of Alla Enrekang in increasing public knowledge about the Islamic Inheritance Law. To achieve these objectives, the researchers used a technique of collecting data through questionnaires, interviews, and documentation. Data have been obtained from the results of the study were processed using quantitative analysis to obtain data regarding the level of knowledge of the villagers Sumillan District of Alla Enrekang on Islamic law, to obtain data about people's knowledge of how the division of inheritance based on the Islamic law of inheritance in the Village Sumillan District of Alla District Enrekang, obtain data on the efforts made by the government Sumillan Rural District of Alla Enrekang in increasing public knowledge about the Islamic Inheritance Law. The results of this study show that: 1) The level of public knowledge Sumillan Rural District of Alla Enrekang of Islamic inheritance law is low. 2) Knowledge of the public about how the division of inheritance based on the Islamic law of inheritance in the Village District of Alla Enrekang Sumillan low. 3) Efforts have been made by the government Sumillan village in order to improve public knowledge about the Islamic law of inheritance is to disseminate directly in the community by holding a seminar on Islamic law.